Development and validation of innovative experiments in organic chemistry based on isolation, structure elucidation and bioactivity testing of new diterpenes from Coleus blumei Benth - Templora, Vilma Fojas (Animo Repository, 1998)
This study is composed of two parts. Part I includes the isolation, structure elucidation and bioactivity testing of secondary metabolites from the chloroform extracts of Coleus blumei Benth. Chromatographic separation of the chloroform extracts of the dried leaves of Coleus blumei Benth. afforded compound 1. The structure of compound 1 was elucidated by extensive 1D and 2D NMR spectroscopy and mass spectrometry. It was found out that compound 1 was a mixture of two diastereomers of a new diterpene. It was bioassayed for antimicrobial activity with the use of the agar cup method and the micronucleus test was done to determine its antimutagenic potential. Compound 1 was found to be antibacterial, antifungal and antimutagenic.Based on the information gathered from the literature and knowledge, skills and techniques acquired from Part I, innovative experiments in organic chemistry were developed and validated for use of B. S. Biology students. These innovative experiments aimed at enriching the organic chemistry course and providing students with basic information on natural products as well as developing their laboratory skills and techniques. Six innovative experiments were developed. They were content validated by experts and their readability level was evaluated using the JB formula. The experiments were found to have reading levels appropriate for the intended users. To determine the possibility of adapting the experiments for enrichment purposes, they were pilot tested on B. S. Biology students at the West Visayas State University in Iloilo City. Results of the evaluation revealed that students were able to develop scientific values and were stimulated to participate actively in laboratory work. They found the experiments informative, enjoyable, interesting, simple and relevant to the course they were enrolled in and to their daily life as well. Based on the findings, the following conclusions were drawn: 1) the chloroform extracts of Coleus blumei Benth. led to the isolation of a mixture of diastereomers of a new and bioactive diterpene and 2) the experiments developed were valid as to content, with reading levels appropriate for its intended users. These experiments were acceptable as perceived by the users.